Genetic gains from 30 years of cassava breeding in Nigeria for storage root yield and disease resistance in elite cassava genotypes - Okechukwu, R.U.; Dixon, Alfred G.O. (Informa UK Limited, 2008)
Cassava (Manihot esculenta Crantz) is crucial for both food security and poverty alleviation in Sub-Saharan Africa (SSA). Cassava improvement for SSA started at the International Institute of Tropical Agriculture in 1970, and several improved lines with different characteristics have been developed to date. The primary focus of breeding work has been to increase root yield, early bulking, tolerance to biotic and abiotic stresses, and increased dry matter content. This paper represents a study of 112 varieties cloned and introduced between 1970 and 2000, and evaluated in 2003 and 2004 to quantify genetic gains in root yield and disease resistance. The genetic gain per year was 1.3% for fresh root yield, 1.2% for dry root yield, 0.65% for cassava mosaic disease resistance, 0.21% for cassava anthracnose disease resistance, and -0.03% for cassava bacterial blight disease resistance. Though there was no statistical significance in the net negative genetic gain in cassava bacterial blight resistance, it is essential that more emphasis be placed on improving this trait to enhance stability and productivity in African environments.